Preclinical optimization of Ly6E-targeted ADCs for increased durability and efficacy of anti-tumor response. Issue 1 (1st January 2021) - Dela Cruz Chuh, Josefa; Go, MaryAnn; Chen, Yvonne; Guo, Jun; Rafidi, Hanine; Mandikian, Danielle; Sun, Yonglian; Lin, Zhonghua; Schneider, Kellen; Zhang, Pamela; Vij, Rajesh; Sharpnack, Danielle; et al.
ABSTRACT: Early success with brentuximab vedotin in treating classical Hodgkin lymphoma spurred an influx of at least 20 monomethyl auristatin E (MMAE) antibody-drug conjugates (ADCs) into clinical trials. While three MMAE-ADCs have been approved, most of these conjugates are no longer being investigated in clinical trials. Some auristatin conjugates show limited or no efficacy at tolerated doses, but even for drugs driving initial remissions, tumor regrowth and metastasis often rapidly occur. Here we describe the development of second-generation therapeutic ADCs targeting Lymphocyte antigen 6E (Ly6E) where the tubulin polymerization inhibitor MMAE (Compound 1 ) is replaced with DNA-damaging agents intended to drive increased durability of response. Comparison of a seco -cyclopropyl benzoindol-4-one (CBI)-dimer (compound 2 ) to MMAE showed increased potency, activity across more cell lines, and resistance to efflux by P -glycoprotein, a drug transporter commonly upregulated in tumors. Both anti-Ly6E-CBI and -MMAE conjugates drove single-dose efficacy in xenograft and patient-derived xenograft models, but seco- CBI-dimer conjugates showed reduced tumor outgrowth following multiple weeks of treatment, suggesting that they are less susceptible to developing resistance. In parallel, we explored approaches to optimize the targeting antibody. In contrast to immunization with recombinant Ly6E or Ly6E DNA, immunization with virus-like particles generated a high-affinity anti-Ly6E antibody. Conjugates to this antibody improve efficacy versus a previous clinical candidate both in vitro and in vivo with multiple cytotoxics. Conjugation of compound 2 to the second-generation antibody results in a substantially improved ADC with promising preclinical efficacy.